Poverty and intergenerational change: Preliminary findings from the round 5 survey in Ethiopia - Woldehanna, T; Araya, M; Pankhurst, A (Young Lives, 2018)
This fact sheet presents findings from the fifth round of the Young Lives survey of children in Ethiopia in 2016. Young Lives is a longitudinal study of childhood poverty that has followed two cohorts of children born seven years apart since 2002. This fact sheet reports on trends in household living standards – measured by a wealth index – and movement into and out of poverty for the Younger Cohort households in 2016 (Round 5 survey) compared to 2002 (Round 1 survey). It also reports on intergenerational mobility between parents and children in terms of education and health for the Older Cohort (aged 22 in 2016). There have been noticeable movements into and out of poverty over time. Of the 1,741 Younger Cohort households interviewed in all five rounds, 584 (33%) were in the bottom tercile (i.e. poor) in 2002, but only 12% of these households have been persistently in the bottom wealth tercile over the five rounds from 2002 to 2016.